Effect of UV dose on degradation of venlafaxine using UV/H2O2: perspective of augmenting UV units in wastewater treatment. Issue 9 (15th April 2020) - Hollman, Jordan; Dominic, John Albino; Achari, Gopal; Langford, Cooper H.; Tay, Joo-Hwa
ABSTRACT: Many water and wastewater treatment plants (WWTPs) are fitted with a UV system that provides post treatment disinfection before the water is released to receiving water. This paper presents a study on expected removal for the pharmaceutical venlafaxine (VEN) in a typical UV unit at a municipal WWTP with analysis of removal rates of an advanced oxidation process using UV irradiation with injection of H2 O2 . The study is supported by bench scale degradation experiments on VEN. Results demonstrated that UV can completely degrade VEN, but the addition of H2 O2 increased pseudo first order rate constant by up to 2.5 times. Extrapolations of the lab data indicated that removal rates of VEN at the UV disinfection unit of a typical municipal WWTP are approximately 0.4% at standard operating conditions. With the addition of 10 mg/L of H2 O2, degradation of VEN can be increased by ten times over existing UV treatment. By studying the impact of adjusting parameters such as UV intensity, UV dosage, and H2 O2 dosage, a framework is set to allow researchers and engineers to move forward with developing UV/H2 O2 systems that meet their future design needs for pharmaceutical removal. GRAPHICAL ABSTRACT: